A qualitative study of the experiences and expectations of women receiving in-patient postnatal care in one English maternity unit - Bick Debra; Rose Val; Beake Sarah; Weavers Annette; Wray Julie (BMC, 2010)
Abstract Background Studies consistently highlight in-patient postnatal care as the area of maternity care women are least satisfied with. As part of a quality improvement study to promote a continuum of care from the birthing room to discharge home from hospital, we explored women's expectations and experiences of current in-patient care. Methods For this part of the study, qualitative data from semi-structured interviews were transcribed and analysed using content analyses to identify issues and concepts. Women were recruited from two postnatal wards in one large maternity unit in the South of England, with around 6,000 births a year. Results Twenty women, who had a vaginal or caesarean birth, were interviewed on the postnatal ward. Identified themes included; the impact of the ward environment; the impact of the attitude of staff; quality and level of support for breastfeeding; unmet information needs; and women's low expectations of hospital based postnatal care. Findings informed revision to the content and planning of in-patient postnatal care, results of which will be reported elsewhere. Conclusions Women's responses highlighted several areas where changes could be implemented. Staff should be aware that how they inter-act with women could make a difference to care as a positive or negative experience. The lack of support and inconsistent advice on breastfeeding highlights that units need to consider how individual staff communicate information to women. Units need to address how and when information on practical aspects of infant care is provided if women and their partners are to feel confident on the woman's transfer home from hospital.